Performance Optimization of Power Plant Waste Heat Using H2O-LiBr Absorption Refrigerant System - Lydia Anggraini; Annisa Nur Wahyuni; Rendi Hernawan; Tetuko Kurniawan (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2022)
This paper examines the use of waste energy in a 3x1 MW Gas Engine Power Plant (GEPP) on Bawean Island, Indonesia. The feasibility method uses water-lithium bromide (H2O-LiBr) technology as absorption refrigeration technology. In addition, bananas are also used for cold storage to overcome waste energy utilization. The cold storage is placed in the 300 m3 area with a 100 kg load capacity for a banana with a temperature of 5oC, 85% humidity, 24 hours of operation, 1292 W cooling load, and 371 TR. This system is used because it utilizes a cheap energy source that dissipates heat from gas and has no ecological hazards, such as ozone layer depletion and global warming. The exhaust gas temperature is 500oC. Moreover, cooling loads for cold storage, which are used with thermodynamic models, and consistent fluid properties, performance, and size of cold storage were also investigated. The results obtained show that higher cold storage output comes from internal factors as compared to external factors. In addition, the absorption refrigerant with Tevaporation is 5oC, capacity 403 TR and Qabsorption is 984 kW, Qgenerator is 1066 kW, Qevaporation is 1411 kW, Qcondenser is 1493 kW, with an absorption coefficient of performance (COP) of 1.32 and power consumption of 158,25 kW. Furthermore, after calculations, analysis, and field experiments, it shows that the internal factor of the cooling load is higher than the external factor sourced from bananas in the cold storage. This phenomenon occurs probably due to the product being refrigerated, following the soar cooling capacity. Thus, the waste energy in PLTGU 3x1 MW has tried to be utilized by the refrigerant absorption system.